The Influence of Body Imagde and Fashion Involvement Towards Luxury Fashion Consumption - Hayuwidi, Cahya Agunging; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2016)
Abstract. Body image is perception of personal physical appearance that can be positive or negative and also leading to body satisfaction or body dissatisfaction. Body satisfaction or dissatisfaction affect individuals in all ages and also have potential to impact lifestyle choices. Most individuals expressed dissatisfaction on their body weight and specifically in their abs area. Through film and various types of advertising both in Indonesia and the world, people are introduced to the figures with high slim women and muscular man. The mass media also create an image as if the slim women and muscular man better than people who fat. In movie, actress that have slim body is the main character. Sometimes women which is overweight and not fashionable, often becoming bullied by the people around but it will eventually turn into a slim beautiful girl that like by the men. This is happened in the movie series Yo Soy Betty la fea in 2000s, which was popular in Indonesia. Fashion consumption influenced by the body image because from the previous research said that, when consumers’ bad body image, if their status is lower too, then their self-brand connection with fashion brands is higher than that of the high status; and when consumers’ self-esteem level is high, the result is opposite. Another variable that is involved in fashion, which also affects the consumption of fashion products, adapted from previous studies, are value consciousness and self-expression through the brand. This research method is the interview for exploratory research and questionnaires with Likert scale, the population is young adults in Indonesia aged between 18-25 years. This research result using exploratory research to define the beauty and body image means among young adults in Indonesia. From the exploratory research, the body image definition in young adults in Indonesia is supported the previous research which is perception of personal physical appearance that can be positive or negative and also leading to body satisfaction or body dissatisfaction. In Indonesia people concern about their body shape, appearance, and also their face and skin. The beauty standard in young adult in Indonesia is when have good inner and outer beauty which means not only physically beautiful or handsome but also have a good personalities. The descriptive research result is that fashion consumption positively influenced by body image, fashion involvement, and self-expression through brand. Variables are adapted from several research with framework, furthermore this research is includes value consciousness which was predicted to positively influence towards fashion consumption turns out to negatively moderate the relationship. With this research, hopefully people can understand future about beauty, body image, in Indonesia and the factors that influence fashion consumption Keywords:body image; beauty; fashion involvement; fashion consumption; value consciousness; self-expression through brand